Crisis leadership and its role in organizational immunity: An exploratory study of the opinions of a sample of faculty members at technical universities in the Kurdistan Region of Iraq - Dino, Chiya; Ismail, Hadi; Nori , Range (Humanities Journal of University of Zakho, 2024)
The research aims to investigate the levels of Crisis Leadership dimensions and Organizational Immunity , to diagnose the role of crisis leadership in organizational immunity in technical universities in the Kurdistan Region of Iraq by analyzing the impact of crisis leadership dimensions on organizational immunity, the descriptive analytical approach was adopted to diagnose the research variables where conducted in(3) from technical universities and the sample consisted of (234) faculty teaching staff in the universities surveyed who expressed their opinion through the levels of their agreement on questionnaire items, which was the main tool for data collection , The data was analyzed based on a number of statistical tools, including mean, standard deviations, correlation coefficient and regression, the research found that there is a significant correlation between crisis leadership and organizational immunity beside that the organizational immunity in universities is associated with the availability of indicators that crystallize within the dimensions of crisis leadership among administrative leaders in the universities surveyed, The research recommended the need for universities to enhance their organizational immunity by focusing on the dimensions of crisis leadership among leaders, especially taking responsibility and learning from the crisis, as well as proposing future studies in other environments and testing crisis leadership skills and other variables that can affect the enhancement of organizational immunity within the framework of future studies.